DNA Methylation Is Responsive to the Environment and Regulates the Expression of Biosynthetic Gene Clusters, Metabolite Production, and Virulence in Fusarium graminearum - Bonner, Christopher; Sproule, Amanda; Rowland, Owen; Overy, David; Subramaniam, Rajagopal (Frontiers in Fungal Biology, 2021)
Histone modifications play a significant role in the regulation of biosynthetic gene clusters (BGCs) in the phytopathogen Fusarium graminearum, by contrast, epigenetic regulation by DNA methyltransferases (DNMTs) is less documented. In this study, we characterized two DNMTs (FgDIM-2 and FgRID) in F. graminearum, with homologies to “Deficient in methylation” (DIM-2) and “Repeat-induced point (RIP) deficient” (RID) from Neurospora. The loss of DNMTs resulted in not only a decrease in average methylation density in the nutrient-poor, compared to nutrient-rich conditions, but also differences in the genes expressed between the WT and the DNMT mutant strains, implicating the external environment as an important trigger in altering DNA methylation patterns. Consequently, we observed significant changes in the regulation of multiple BGCs and alterations in the pathogenicity of the fungus.